Graduating in a pandemic context and relative employability: What have we learned from graduates’ statements in the media? - Suleman, F. (ICERI2020 Proceedings, 2020)
This study explores 20 online news articles, which comprise statements from soon-to-be graduates (n= 33) on the difficulties faced or perceived in the current hostile labour market in both European and non-European countries. The students are under the age of 25 of a bachelor or master’s degree in hard or soft fields of education. Preliminary findings reveal four situations that we label as 4Ds, Discouraged, Dismissed, Delayed, and Distanced. The first group have a negative perception of their employability; the Dismissed is made up of students whose job offer has been cancelled; the contracts of the Delayed group have been suspended; and the Distanced group’s jobs have changed to remote work. The sampled soon-to-be graduates describe the multiple consequences of the unfavourable labour market in their lives, notably psychological distress, administrative issues, and economic burden.